Socially Responsible or Merely a Public Stunt? CSR, Skepticism, and Company Evaluation of Cigarette Companies - Adelina Proboyo; Lysander Darrell Wijaya Oeij; Antonio Darrell Pangadian; Fandy Tjiptono (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Corporate Social Responsibility (CSR) has become a strategic tool for companies in controversial industries to enhance their public image. Indonesian cigarette manufacturers frequently engage in CSR initiatives, raising public scrutiny over whether these actions are genuine or reputation-driven. Understanding how the public evaluates these initiatives is therefore important. Unlike prior studies that treat CSR as a single construct, this research compares the effects of various CSR types and examines the mediating role of skepticism towards CSR in a controversial industry in Indonesia. Purpose: This research aims to examine the effect of different CSR initiatives (health, environment, sports, and education) on public skepticism, and how skepticism, in turn, affects company evaluation. Method: An experimental study was conducted with 144 participants randomly assigned to one of four CSR initiatives. Participants received information about Rokoqu, a hypothetical cigarette company, its CSR initiatives, and tobacco-related health risks. Data were analyzed using mediated regression analysis with SPSS and PROCESS Macro. Findings: Skepticism towards CSR affected company evaluation negatively. However, CSR types did not significantly influence skepticism, indicating no mediating effect. Health- and education-related CSR did not differ significantly in influencing company evaluation, while environment- and sports-related CSR resulted in significantly lower evaluations than health-related CSR. Conclusions: While CSR types do not trigger skepticism, they affect company evaluation differently. Environment- and sports-related CSR influence company evaluation more negatively than health and education-related CSR. Research implication: CSR programs may backfire for companies in controversial industries, especially if the initiatives are misaligned with their reputation and public expectations.